Transfer of miR-877-3p via extracellular vesicles derived from dental pulp stem cells attenuates neuronal apoptosis and facilitates early neurological functional recovery after cerebral ischemia-reperfusion injury through the Bclaf1/P53 signaling pathway - Yan Miao; Xin Liang; Jigang Chen; Hongyi Liu; Zilong He; Yongkai Qin; Aihua Liu; Ruxu Zhang (Elsevier, 2024)
Cerebral ischemia-reperfusion injury (I/RI) is one of the principal pathogenic factors in the poor prognosis of ischemic stroke, for which current therapeutic options to enhance neurological recovery are notably insufficient. Dental pulp stem cell-derived extracellular vesicles (DPSC-EVs) have promising prospects in stroke treatment and the specific underlying mechanisms have yet to be fully elucidated. The present study observed that DPSC-EVs ameliorated the degree of cerebral edema and infarct volume by reducing the apoptosis of neurons. Furthermore, the miRNA sequencing and functional enrichment analysis identified that miR-877-3p as a key component in DPSC-EVs, contributing to neuroprotection and anti-apoptotic effects. Following target prediction and dual-luciferase assay indicated that miR-877-3p interacted with Bcl-2-associated transcription factor (Bclaf1) to play a function. The miR-877-3p inhibitor or Bclaf1 overexpression reversed the neuroprotective effects of DPSC-EVs. The findings reveal a novel therapeutic pathway where miR-877-3p, transferred via DPSC-EVs, confers neuroprotection against cerebral I/RI, highlighting its potential in promoting neuronal survival and recovery post-ischemia.